Constraints to the Implementation of Climate Change Adaptation Measures by Farmers in Delta State, Nigeria (Global Journal of Science Frontier Research, 2012)
This study examined constraints to the implementation of climate change adaptation measures by farmers in Delta North Agricultural Zone of Delta State, Nigeria. Crop farmers in three purposively selected extension blocks served as respondents of the study. A sample of 321 respondents was used for the study. A list of farmers in contact with extension served as sampling frame. Data for the study were collected from the respondents of the study through the use of a detailed, carefully designed and validated interview schedule. Trained field assistants selected in each location in addition to the researchers collected the data for the study. Data generated by the study were analyzed using descriptive statistics. Results show that there were more male crop farmers in the area of study. Also, majority (92%) of the respondents had formal education and many years of farming experience. The study found that respondents were using some adaptation measures which include: the use of crop rotation, use of sandbags at river banks, use of bamboo stakes, planting of cover crops and the construction of drainages.